2002
DOI: 10.1042/bj3620013
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of capacitative and non-capacitative Ca2+ entry in A7r5 vascular smooth muscle cells: only the latter operates during receptor activation

Abstract: In A7r5 vascular smooth muscle cells, Arg8-vasopressin (AVP) stimulates phospholipase C leading to activation of two distinct Ca2+ entry pathways. The capacitative Ca2+ entry (CCE) pathway is activated by depletion of Ca2+ stores, is permeable to Mn2+, Ba2+ and Ca2+, and is selectively blocked by Gd3+ (1μM). A7r5 cells also express a non-capacitative Ca2+ entry (NCCE) pathway, which is activated by arachidonic acid that is released by the sequential activities of phospholipase C and diacylglycerol lipase. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 0 publications
11
56
2
Order By: Relevance
“…2ϩ Entry-Depolarization (by the addition of HBS containing 53 mM KCl in place of NaCl) stimulated an increase in [Ca 2ϩ ] i which was prevented by 100 nM nimodipine or 10 M verapamil and potentiated by 100 nM BAYK8644, confirming the involvement of L-type Ca 2ϩ channels (39,49) (Fig. 5A).…”
Section: Inhibition Of Ac By Camentioning
confidence: 64%
See 2 more Smart Citations
“…2ϩ Entry-Depolarization (by the addition of HBS containing 53 mM KCl in place of NaCl) stimulated an increase in [Ca 2ϩ ] i which was prevented by 100 nM nimodipine or 10 M verapamil and potentiated by 100 nM BAYK8644, confirming the involvement of L-type Ca 2ϩ channels (39,49) (Fig. 5A).…”
Section: Inhibition Of Ac By Camentioning
confidence: 64%
“…Our initial intention had been to explore the relative effectiveness of Ca 2ϩ entry via CCE and NCCE pathways in causing inhibition of AC, but we began our experiments (and then continued) using a variant of the cell line in which AVP neither inhibits CCE nor activates NCCE (39). In the cells used for this study, therefore, all AVP-evoked Ca 2ϩ entry is mediated by CCE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reciprocal regulation of AA-activated NSOCE and SOCE has been reported by several authors (36,37,69,70). It has been suggested that AA coordinates the contribution of different receptor-regulated pathways such that each is activated in a specific temporal sequence.…”
Section: Discussionmentioning
confidence: 77%
“…It has been suggested that AA coordinates the contribution of different receptor-regulated pathways such that each is activated in a specific temporal sequence. By activating NSOCE, and simultaneously inhibiting SOCE, AA ensures that, when the extracellular stimulus is present, only the NSOCE pathway contributes to Ca 2+ entry whereas SOCE contributes only after removal of the stimulus (37). The mechanisms underlying this phenomenon are still unclear.…”
Section: Discussionmentioning
confidence: 99%